The origin a ritual elements of Tengrism and the cult of the Sky - Сaпaшев, О. С.; Шaргыновa, A. Е. (Journal of Oriental Studies, 2017)
The origins of Tengrism are considered in the article. Tengrism is defined as a worldview, which includes the religious idea. The main features of tengrism forming the basis of the spiritual culture of the Turks are distinguished in the article. In the view of it, the etymology of the word “Tengri” is analyzied from various researchers’ points of view. Meanwhile, the article presents an attempting to show the parallel between Turkic Tengrism and Chinese cult of the sky, as these two worldviews have an obvious similiarities. The analysis is made on whetherone worldview was the source of formation of another or whether these two worldviews are not interdepended and existed separately.